1996
DOI: 10.1073/pnas.93.17.8836
|View full text |Cite
|
Sign up to set email alerts
|

Zinc- and iron-rubredoxins from Clostridium pasteurianum at atomic resolution: a high-precision model of a ZnS4 coordination unit in a protein.

Abstract: The Zn(S,ys)4 unit is present in numerous proteins, where it assumes structural, regulatory, or catalytic roles. The same coordination is found naturally around iron in rubredoxins, several structures of which have been refined at resolutions of, or near to, 1 A. The fold of the small protein rubredoxin around its metal ion is an excellent model for many zinc finger proteins. Zn-substituted rubredoxin and its Fe-containing counterpart were both obtained as the products of the expression in Escherichia coli of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
179
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(197 citation statements)
references
References 38 publications
17
179
1
Order By: Relevance
“…Similar observations have been reported for recombinant Rds heterologously overproduced in E. coli in which zinc occupies the iron site (32)(33)(34)(35). 2 We used the ironenriched triple variant (prepared by supplying 150 -200 M FeCl 3 in the growth medium during overexpression) in the following analyses.…”
Section: Resultsmentioning
confidence: 76%
“…Similar observations have been reported for recombinant Rds heterologously overproduced in E. coli in which zinc occupies the iron site (32)(33)(34)(35). 2 We used the ironenriched triple variant (prepared by supplying 150 -200 M FeCl 3 in the growth medium during overexpression) in the following analyses.…”
Section: Resultsmentioning
confidence: 76%
“…Residues relevant to this study are indicated. The drawing was generated using Rasmol, from coordinates in file 1IRO in the Protein Data Bank [34] Bonomi et al intensities at 495 nm, and scaling to the corresponding spectral intensities of the appropriate holoRd Electrospray ionization mass spectrometry (ESI-MS) spectra of apoRds, holoRds or a mixture containing apoRd, 6 M chaotrope and stochiometric iron. Right: CpRd (6 M urea as the chaotrope).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The refinement of one of these, from Desulfovibrio vulgaris, has been extended to a 1.0-Å resolution (38), and that data set was used in a study describing the application of direct methods to protein crystallography (39). All of those studies indicated that rubredoxins contain a very small three-stranded antiparallel ␤-sheet, a hydrophobic core, and several loops (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…That analysis, carried out at a resolution of 1.5 Å, featured the first report of a least-squares refinement of a protein at a truly atomic level. The structural analysis of rubredoxin from C. pasteurianum was eventually extended to 1.2-Å resolution (31) and 1.1-Å resolution (32), and other rubredoxin structures have been reported over the years from other mesophilic (room temperature) organisms (33)(34)(35)(36)(37)(38)(39)). The refinement of one of these, from Desulfovibrio vulgaris, has been extended to a 1.0-Å resolution (38), and that data set was used in a study describing the application of direct methods to protein crystallography (39).…”
mentioning
confidence: 99%